One-pot foam-gelcasting/nitridation synthesis of high porosity nano-whiskers based 3D Si3N4 porous ceramics - Han, Lei; Chen, Yu; Chang, Hong; Li, Faliang; Liu, Cheng; Shyng, Tommy; Zhu, Yanqiu; Li, Guangqiang; Zhang, Haijun; Jia, Quanli; Zhang, Shaowei (Journal of the European Ceramic Society, 2021)
[Display omitted] •Nano-whiskers based 3D Si3N4 porous ceramics (3D-NWSNPC) were prepared via a facile one-pot foam-gelcasting/nitridation route at 1423–1523 K.•3D-NWSNPC showed excellent thermal conductivity, and a certain degree of recoverability under cyclic compressive loading.•The sample with solid loading of 12.5 wt% exhibited the highest compressive strength of 1.9 MPa, even though its porosity was high up to about 91 %. Nano-whiskers based 3D Si3N4 porous ceramics (3D-NWSNPC) with high-porosity (about 91–93 %), low density (0.17–0.25 g/cm3), low thermal conductivity, and a certain degree of recoverability under cyclic compressive loading and reasonably strengths were prepared at 1423–1523 K via a one-pot foam-gelcasting/nitridation route using inexpensive commercial Si powders as starting materials and hexadecyl trimethyl ammonium bromide as foaming agent. After nitridation at 1523 K, the sample with an original solid loading of 12.5 wt% exhibited the highest compressive strength of 1.9 MPa, even though its density was lowered to 0.25 g/cm3. The sample nitrided at 1473 K had a relative density of 7.3 %. Its compressive and specific strength were respectively 1.1 MPa and 5.5 MPa·cm3 g−1, and its thermal conductivity was as low as 0.074 W/(m K) (measured at 323 K). These outstanding properties would make the as-prepared 3D-NWSNPC a promising candidate for applications in catalysis, filtration, thermal insulation and many other important areas.